2007
DOI: 10.1556/avet.55.2007.3.9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of goose serum amyloid a acute phase response by enzyme-linked immunosorbent assay

Abstract: Serum amyloid A (SAA) is of interest as the circulating precursor of amyloid A protein, the fibrillar component of AA (secondary) amyloid deposits, and also as an extremely sensitive and rapid major acute phase protein. Serum concentrations of acute phase proteins (APPs) provide valuable information about the diagnosis and prognosis of various diseases, and thus the relevance of APPs for monitoring the health status of domestic animals is widely accepted. More importantly, the measurement of SAA concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, Chamanza et al (1999) demonstrated that perhaps SAA is a reliable APP for diagnosing inflammatory lesions in chickens. The expression of SAA also could be increased by bacterial and viral infection such as with Pasteurella multocida , Staphylococcus aureus and infectious bronchitis virus ( Chamanza et al, 1999 ; Kovacs et al, 2007 ; Asasi et al, 2013 ). In our study, C. perfringens challenge with a high fishmeal diet, rather than infection alone, resulted in a higher intestinal lesion score and increased the relative abundance of C. perfringens at 1 dpi that was accompanied by an increase in AGP and SAA increase in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Chamanza et al (1999) demonstrated that perhaps SAA is a reliable APP for diagnosing inflammatory lesions in chickens. The expression of SAA also could be increased by bacterial and viral infection such as with Pasteurella multocida , Staphylococcus aureus and infectious bronchitis virus ( Chamanza et al, 1999 ; Kovacs et al, 2007 ; Asasi et al, 2013 ). In our study, C. perfringens challenge with a high fishmeal diet, rather than infection alone, resulted in a higher intestinal lesion score and increased the relative abundance of C. perfringens at 1 dpi that was accompanied by an increase in AGP and SAA increase in liver.…”
Section: Discussionmentioning
confidence: 99%
“…Tracheitis, bronchitis, tracheal oedema, bronchial caseous plugs and air sacculitis indicates widespread inflammatory reaction in IBV this causes release and elevation of SAA and Hp concentrations. Kovacs et al (2007) showed a mild increase in SAA in the goose by administration of a fowl cholera vaccine containing inactivated Pasteurella multocida. Vaccination was an inflammatory factor and produced increased SAA levels.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, C-reactive protein (CRP) in dogs and serum amyloid A (SAA) in cats have been routinely tested in small animal clinics as measurement kits have been commercialized. Known avian APPs include SAA, alpha-1 acid glycoprotein, ceruloplasmin, transferrin, fibrinogen, and haptoglobin (8)(9)(10)(11)(12)(13)(14)(15). Among these avian APPs, SAA has been the focus of research because it is a precursor of the amyloid A (AA) protein.…”
Section: Introductionmentioning
confidence: 99%